Powtoon-Based Animated Videos as Learning Media for Science Content for Grade IV Elementary School - Barbara, Ni Kadek Rika; Bayu, Gede Wira (International Journal of Elementary Education, 2022)
The lack of availability of innovative learning media that is able to help describe the material effectively has an impact on the low motivation to learn and students' understanding of the material. Innovative learning media are needed that can improve the quality of learning and create a more meaningful learning process for students. The purpose of this research is to design a media development process, to develop media that has been tested for validity, and to find out the responses of teachers and students to the animation video based on Powtoon learning media. This research is development research. The development model used is the ADDIE model. The data collection method used is a questionnaire/questionnaire method to collect data from the results of reviews from test experts, teacher trials, and students. The subjects of this research are 2 material experts, 2 media experts, and 2 practitioners. The object of this research is the validity of the animation video based on Powtoon. The data analysis technique used in this research is the descriptive qualitative analysis and descriptive quantitative analysis. The results showed that the quality of the media was in the very valid category with a score of 4.68, this indicates that the developed media is suitable for use in the good category, so it is worthy of being used as a reference to overcome the problem of lack of innovative media. The developed media deserves to be used in a good category. So that the animation video learning media based on Powtoon on the topic of animal life cycles in class IV deserves to be used as a reference in overcoming the problem of lack of innovative media. The implication of this research is the existence of an animation video based on Powtoon on the topic of animal life cycles in grade IV Elementary School with "very valid" quality and can be used in the learning process on science content.